Anti-HCV drugs in the pipeline - Yang, Priscilla L. (2011)
Several directly-acting and host-targeting antivirals that inhibit hepatitis C virus replication have entered clinical trials. Amongst the most advanced of these are RG7128, an inhibitor of the NS5B polymerase; BMS-790052, an inhibitor of NS5A; and alisporivir, an inhibitor of human cyclophilins. These agents have potent antiviral activity in chronic HCV patients, act additively or synergistically with inhibitors of the HCV NS3/4A protease, and improve the rate of virologic response produced by traditional pegylated interferon plus ribavirin therapy. No cross resistance has been observed; moreover, nucleoside NS5B and cyclophilin inhibitors appear to suppress resistance to non-nucleoside NS5B and NS3/4A inhibitors. Several recent reports of virologic responses produced by combinations of agents that inhibit HCV replication in the absence of interferon provide optimism that eradication of HCV will be possible without interferon in the future.